Tristetraprolin, Inflammation, and Metabolic Syndrome in Arab Adults: A Case Control Study - Nasser M. Al-Daghri; Albatul Y.A. Al-Shuwaie; Amani Alghamdi; Osama E. Amer; Malak N.K. Khattak; Mohammed G.A. Ansari; Abdullah M. Alnaami; Shaun Sabico (Biology, 2021)
Tristetraprolin (TTP) is an mRNA binding protein suggested to have a substantial role in regulating the mRNA expression of numerous inflammatory factors, but data on TTP and its association with metabolic syndrome (MetS), a chronic low-grade inflammatory disorder, are scarce. We hypothesize that TTP may modulate MetS and its components. A total of 200 Saudi adults (aged 38.6 ± 8.3 years) were included in this cross-sectional study. Anthropometrics data were collected and fasting blood glucose taken for the assessment of glycemic, lipids and inflammatory markers using commercially available assays. The National Cholesterol Education Program Adult Treatment Panel (NCEP ATP III) criteria were used to define MetS. Results showed significantly higher levels of TTP in the MetS group than in controls [288.1 pg/mL vs. 150.9 pg/mL, p < 0.001]. Circulating TTP was significantly associated with tumor necrosis factor alpha [TNF-α, R = 0.30, p < 0.05], interleukin 1β [IL-1β, R = 0.41, p < 0.01] and C-reactive protein [CRP, R = 0.36, p < 0.01], adiponectin [R = 0.36, p < 0.05], insulin [R = 0.37, p < 0.05], and insulin resistance [HOMA-IR, R = 0.40, p < 0.05]. Receiver operating characteristics (ROC) suggest a potential use of TTP as diagnostic biomarker for MetS [AUC = 0.819, p < 0.001]. The findings suggest that TTP is associated with inflammation and glycemia, which may influence MetS. TTP is a promising diagnostic biomarker for MetS which can be confirmed in larger cohorts.